2013
DOI: 10.1039/c2dt31788e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the nanoparticle synthesis method on dendronized iron oxides as MRI contrast agents

Abstract: Aqueous suspensions of dendronized iron oxide nanoparticles (NPs) have been obtained after functionalization, with two types of dendrons, of NPs synthesized either by coprecipitation (leading to naked NPs in water) or by thermal decomposition (NPs in situ coated by oleic acid in an organic solvent). Different grafting strategies have been optimized depending on the NPs synthetic method. The size distribution, the colloidal stability in isoosmolar media, the surface complex nature as well as the preliminary bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
77
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 60 publications
8
77
0
Order By: Relevance
“…Indeed, peak shoulders were observed at 1045 cm À1 and 938 cm À1 respectively. This is in accordance with previous results, 40,47,49 and conrms the involvement of the phosphonate group in the chelation. However, the band at 993 cm À1 was not fully attenuated aer complexation with MnO, suggesting that a certain fraction of unreacted phosphonate groups is still present aer reaction with MnO.…”
Section: Physico-chemical Surface Analysis Of Mno@pdn Particlessupporting
confidence: 94%
“…Indeed, peak shoulders were observed at 1045 cm À1 and 938 cm À1 respectively. This is in accordance with previous results, 40,47,49 and conrms the involvement of the phosphonate group in the chelation. However, the band at 993 cm À1 was not fully attenuated aer complexation with MnO, suggesting that a certain fraction of unreacted phosphonate groups is still present aer reaction with MnO.…”
Section: Physico-chemical Surface Analysis Of Mno@pdn Particlessupporting
confidence: 94%
“…Previously 6b, 15 and currently reported studies clearly highlight that the dendritic organic coating impacts the aggregation state of the nano-objects, thus influencing the bioelimination speed and importance of the hepatobiliary versus urinary elimination pathway: NPs covered with small dendrons (this study) are more rapidly and completely eliminated within 24 hours post-IV, predominantly by urinary elimination.…”
mentioning
confidence: 81%
“…14 X-ray and selective area electron diffraction (SAED) measurements showed that they display the typical iron oxide spinel structure. 15 The NP@OA were in situ coated with oleic acid and formed a monodisperse and stable hexane suspension as observed in Fig. 1b.…”
mentioning
confidence: 90%
“…71,72 In vivo and in vitro MRI measurements showed that the contrast enhancement properties of the dendronized NPs were higher than those obtained with commercial polymer-coated NPs (Figure 3). 22 Figure 3: a) Synthetic scheme of NCDs, b) Spin echo T2 weighted axial images sequentially acquired before and after an injection of 650 µl of NCDs at 7T with a small animal dedicated MRI (Biospin -Brücker®). Reproduced from Ref.…”
Section: Performance Of Ncds In Bionanomedicine and As Nanocarriers Imentioning
confidence: 99%